Prevention, diagnosis, and management of atrioesophageal fistula. Issue 7 (1st June 2020) - Gianni, Carola; Della Rocca, Domenico G.; MacDonald, Bryan C.; Mohanty, Sanghamitra; Quintero Mayedo, Angel; Sahore Salwan, Anu; Trivedi, Chintan; Natale, Andrea
Abstract: Atrioesophageal fistula (AEF) is a rare but deadly complication of radiofrequency ablation for atrial fibrillation. Given its rarity, the diagnosis of AEF is usually delayed with a wide variation in management strategies, which contribute to the high mortality associated with AEF. As such, the most important step of AEF management is prevention, whereas early diagnosis and treatment are crucial to reduce its associated high mortality.